Deteksi Dini Kesehatan Warga RT 02 RW 08 Dusun Rogomulyo Kabupaten Semarang Sebagai Upaya Antisipasi Fatalitas Covid-19 - Desti Christian Cahyaningrum; Susanti Pudji Hastuti; Dinar Putri Rahayu; Ft. Dea Elma Eldiana; Anissa Diti Kurniasari; Yunita Tri Utami (Universitas Kristen Satya Wacana Salatiga, 2022)
COVID-19 has a low fatality rate but has developed into a pandemic due to its highly infectious nature. Nonetheless, COVID-19 fatality is increasing in patients with a history of comorbidities. Based on survey, it was concluded that the understanding of the residents of RT 02 RW 08 Dusun Rogomulyo, Semarang Regency regarding the comorbid COVID-19 was still lacking. In addition, there was the limited funds as problem among residents to carry out medical check-up regularly. Therefore, it was necessary to increase the understanding and detection of the comorbid COVID-19 presence in these community groups. This Community Service consists of four stages of activities, including survey, health education, free medical check -up, and data analysis. The free medical check-up produced the existing comorbid COVID-19 information in this community group as its activity output, namely cardiovascular disease, especially hypertension (51.1%) and cholesterol (20%). This information supports socialization activities and was able to foster understanding and awareness of citizens to better maintain their health conditions, especially related to the comorbidity of COVID-19.